Hedging Maritim Indonesia di Tengah Persaingan Strategis India-China - Kurniawan, Dwiki; Puspitasari, Irfa (Universitas Diponegoro, 2017)
This research inisiated from the ehancement of Indonesia-India’s maritime cooperation in 2015. Indonesia and India has great role in their region. Every aspect of their policy reflecting their own national interest and strategy. These enhancement become interesting because its need to explain by geopolitic and geostrategy point of view. The author try to explain the reasons of enhancement base on maritime geopolitic and geostrategy. This research believe that theory of hedging strategy and theory of maritime sea power could be the best answer to this issue. To give the reasons of enhancement, this reaserch has time range between 2001-2005. This research argues that the enhancement is caused by Indonesia’s hedging strategy in the middle of strategic rivalry between two great powers in region.By cooperation with both India and China, Indonesia use hedging strategy to face the uncertainty condition by India and China competition in Indian Ocean. Through hedging strategy, Indonesia could also implementating his ambition of sea power and maintain his chokepoint security.Keywords: Hedging, Maritim, Indonesia, India, China, Strategic Rivalry